Non-Equilibrium Ionic Liquid-Electrode Interface at Elevated Temperature and Its Influence on Co2+ Reduction Process. Issue 8 (17th May 2016) - Tułodziecki, M.; Tarascon, J.-M.; Taberna, P.-L.; Guéry, C.
Abstract : Electrodeposition in Ionic Liquid (IL) media is still at its infancy stage. Recently much attention is devoted to exploration of the IL-electrode interface for better understanding of the electrochemical processes at the electrified surfaces. Herein, we provide a new perspective of the temperature-driven IL-substrate interface structuring. We observed an increase in Co 2+ reduction kinetics induced by applying a high temperature gradient. In contrast, keeping the cell at a high constant temperature (100°C) leads to slower Co 2+ reduction kinetics, it results in a shift of the reduction onset and evolution of the cyclic voltammogram shape with time. We could ascribe these phenomena to the disturbance of the electrochemical double layer (induced by heating) and its further slow reorganization at constant temperature. We showed that such non-equilibrium behavior can be beneficial for the synthesis of metallic thin films from ILs. Electrochemical quartz crystal microgravimetry, impedance spectroscopy, cyclic voltammetry and chronoamperometry were employed within this work.